ANALYZING STUDENTS’ PERCEPTION OF ONLINE LEARNING FOR ENGLISH SPEAKING SKILLS - Utary Rustam; Nurazizah Nurazizah (Al-Irsyad: Journal of Education Science, 2023)
Online learning for English-speaking skills emerged as an alternative mode of instruction during the COVID-19 pandemic and created learning conditions that differ from conventional face-to-face classrooms. This study aimed to describe students’ perceptions toward online learning for English-speaking skills. The research employed a descriptive quantitative design. The participants of this study were English department students at the State Islamic Institute of Parepare. Data were collected using a questionnaire designed to measure students’ perceptions of online learning for speaking skills. The collected data were analyzed quantitatively by calculating mean scores and frequencies. The findings revealed that the mean score of students’ perception toward online learning for English speaking skills was 79, indicating a positive perception. Furthermore, students’ perceptions were categorized into two main aspects, namely learning facilities and teaching methods. Overall, the results suggest that online learning was perceived as effective in supporting students’ English speaking skills during the online learning process.